2015
DOI: 10.4031/mtsj.49.1.9
|View full text |Cite
|
Sign up to set email alerts
|

In situ Tagging of Nassau Grouper Epinephelus striatus Using Closed-Circuit Rebreathers at a Spawning Aggregation in Puerto Rico

Abstract: Acoustic telemetry is a widely used technique employed to better understand fish movement patterns across seascapes. Traditionally, surgical acoustic transmitter implantation is conducted at the surface, resulting in a high degree of uncertainty as to the post-release survival of the fish and the validity of the results attained from these experiments. Few studies have conducted In situ tagging, where the capture, tagging, and release are completed entirely at the depth in which the fish occurs naturally. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…() and Tuohy et al. (). Fish were retrieved from the traps by using a plastic‐coated net and were held ventral side up with the eyes covered, inducing a catatonic state considered to be an ethical alternative to sedatives (Lowerre‐Barbieri et al.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…() and Tuohy et al. (). Fish were retrieved from the traps by using a plastic‐coated net and were held ventral side up with the eyes covered, inducing a catatonic state considered to be an ethical alternative to sedatives (Lowerre‐Barbieri et al.…”
Section: Methodsmentioning
confidence: 97%
“…All fish were captured using baited chevron traps. Tagging was performed in situ (12-34 m) to reduce fish stress, similar to methods described by Feeley et al (2018) and Tuohy et al (2015). Fish were retrieved from the traps by using a plastic-coated net and were held ventral side up with the eyes covered, inducing a catatonic state considered to be an ethical alternative to sedatives (Lowerre- Barbieri et al 2014).…”
Section: Acoustic Taggingmentioning
confidence: 99%
“…In this study, there were several variables that could not be included in the initial hazards model because of correlation, but their inclusion and limited in uence in the subsequent boat tagged and in situ tagged models reinforced that the tagging method was the most important factor in risk of disappearance from the array. Acoustic tracking data of in situ surgically tagged sh from two other telemetry studies also demonstrate the bene t of tagging method, indicated by high survival rates (97%-100%) post-surgery (Tuohy et al 2015, Bryan et al 2019. The decrease in probability of presence of boat-tagged sh could be due to several factors.…”
Section: Resultsmentioning
confidence: 83%
“…In this study, there were several variables that could not be included in the initial hazards model because of correlation, but their inclusion and limited in uence in the two subsequent models assessing hazards to the boat-tagged and in situ tagged sh independently reinforced that the tagging method was the most important factor for survivorship. Acoustic tracking data of in situ surgically tagged sh from two other studies also indicated high survival rates (97-100%) post-surgery (Tuohy et al 2015, Bryan et al 2019).…”
Section: Discussionmentioning
confidence: 82%